Evaluation of vinorelbine-based chemotherapy as the second or further-line treatment in patients with metastatic breast cancer - Cybulska-Stopa, Bożena; Ziobro, Marek; Skoczek, Marta; Kojs-Pasińska, Ewelina; Cedrych, Ida; Brandys, Anna (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study: The study examined the response rate, response duration and toxicity of vinorelbine and fluorouracil or vinorelbine alone in pretreated metastatic breast cancer. Material and methods : Between June 2001 and September 2009, a group of 103 patients with locally advanced or metastatic breast cancer, who had progressed after anthracycline/taxane chemotherapy, was treated with a vinorelbine-based regimen. The treatment consisted of vinorelbine 25 mg/m 2 and 5-fluorouracil (5-FU) 500 mg/m 2 administered intravenously on days 1 and 8 of each cycle (53 patients) or vinorelbine alone at a dose of 30 mg/m 2 on day 1 and 8 of the cycle, every 3 weeks (50 patients). Patients received chemotherapy as a second or further line of therapy. Treatment was continued until disease progression or unacceptable toxicity. The median age of patients treated with vinorelbine with 5FU was 54 years (range 38–76), and 55.5 years (range 38–73) in the group receiving vinorelbine monotherapy. A total of 417 cycles of chemotherapy were administered – 177 cycles of vinorelbine with 5-FU and 137 cycles of vinorelbine monotherapy. Patients were treated for a median of 4 cycles (range: 1 to 11 cycles). The evaluation of treatment effect was possible in 93 patients (10 patients received only one treatment cycle). Results : The overall response rate (ORR) was 17% (7), including 2 (4%) complete responses (CR) and 5 (10.5%) partial responses (PR). Stable disease (SD) was observed in 50% of patients receiving vinorelbine with 5-FU (24 patients). In a group receiving vinorelbine alone the ORR was 20% (9), including 9 PR (20%) and 16 SD (35.5%). The median time to progression (TTP) for the entire group was 18 weeks (95% CI), 22 weeks among patients treated with vinorelbine with 5-FU and 16 weeks for a second group. The most common hematologic adverse events were neutropenia (20% of cycles) and thrombocytopenia (4%), with grade 3/4 incidence of 8% and 1.5% [according to National Cancer Institute Common Toxicity Criteria (NCI CTC)]. Nausea and vomiting were the most frequent non-hematologic forms of toxicity, occurring in 13% of cycles. The doses of cytotoxics were reduced in 26 (25%) cases. There were no treatment-related deaths. Conclusions : Vinorelbine alone or in combination with 5-FU is an effective and safe treatment for pretreated advanced/ metastatic breast cancer patients. The combination of vinorelbine with 5-FU appears to be a more efficacious regimen than vinorelbine alone.